Sexual initiation in adolescente: women’s life narratives (Research, Society and Development, 2020)
Introduction: Sexual initiation is a remarkable episode in adolescence and (re) remembered in the adult life of women. Objective: To apprehend the experience of sexual initiation of women in adolescence. Methodology: Descriptive, qualitative research, used the life narra tive method. 08 women attended at a Basic Health Unit participated. The data collection was carried out from March to May 2018. The guiding question of the study was: “Tell me about your life that has to do with your sexual initiation ”. For data treatment, thematic analysis was used. Results: It was evidenced that all started their sexual activities in the adolescence period, without using condoms and four of them, became pregnant. They all knew of a contraceptive method and had used at least one of them, even if incorrectly. Conclusion: The importance of training health professionals involved in reproductive planning activities and in preventing STIs in all stages of the woman's life cycle, especially in adolescence, is emphasized.